Development of Media Matching Box to stimulate symbolic thinking skills in children aged 4-5 years - Iis Uswatun Hasanah; Imam Tabroni; Benjamin Brunel; Milton Alan (Yayasan Adra Karima Hubbi, 2023)
This study aims to develop Matching Box media to improve symbolic thinking skills in children aged 4-5 years at Hidayatul Islamiyah Kindergarten. The development model used in this study is Borg and Gall which has been simplified into 6 stages consisting of: Needs Analysis, Planning, Initial Product Development, Learning Media Revision, Field Testing, Final Media Revision. The developed media was validated by 1 material expert and 1 media expert before being tested on children. The trial subjects of this study were 11 children. The instruments used to collect data are learning achievement tests, and observations. the results of the learning test and pretest observation obtained a classical percentage of 72.7% Developing According to Expectations (BSH) and 27.3% Starting to Develop (MB) and the results of the study test and posttest observation obtaining a classical percentage of 90.9% could be categorized as 'Very Well Developing (BSB)' and 9.1% of children were categorized as 'Beginning to Develop (MB)'. From these results, it can be concluded that the Matching Box media is appropriate to be used to improve the symbolic thinking skills of children aged 4-5 years